The Problem of Globalization in the Arkounian Thought - Altawallbeh, Mohammad (Jordan Journal of Social Sciences, 2020)
It has become evident that new or renewed consciousness problems, related to globalization, are connected with some anxious questions concerning Arab-Islamic Identity which is imposed voluntarily or involuntarily on the global thought, modernity, science and the different schools of thought in which the past is reflected strongly in the present. This situation calls for a redefinition, deconstruction and criticism of the past so as to re-understand and digest it based on the appropriate and accurate method of scientific view, with the guidance of the new epistemic foundations, which could reshape its role in our lives, and to stop the persistent questions about any epistemological or historical values that this heritage may represent in the life of people. Yet, the majority of Arab thinkers, pioneered by Arkoun, concerned about contemporary Arab thought, believe that the road map to possess a mental and non-mental modernity requires starting with the completion of the precondition related to globalization, that pushes on reality: epistemologically, ideologically, interpretively, religiously and historically on the level (calling, reading, deconstruction, critique, interpretation and methodology), because these levels of understanding from the point of view of these thinkers are intuitional from the requirements of the theoretical and philosophical conditions. Indeed, each strategy has its approach for the problems posed by globalization and lay the foundations for true relationships and to possess it epistemically. As his intellectual and critical project has been determined by being a project of heritage, that seeks to the completion of the terms of the emergence of globalization in the Arab-Muslim space, the main goal of my research is to identify the basic features of the concept of globalization in his thought and to digest his position from the shape of the proper epistemological relationship that should be built with globalization. In this regard, he worked hard to present globalization, in the light of people thought and to explain the mechanisms of Arab minds that which were produced by, where he sought to achieve this goal, relying on critical thinking in order to determine epistemological and methodological flaw in dealing with globalization, as well as to highlight the strengths and creativity in globalization. The main problems in this research took place by the determination that sought to approach the thought of Arkoun, and to dive in two epistemological moments he was always concerned about: the moment of applying his vision in the right methods to accomplish the restoration of the reality of globalization, then the moment of building rightly the phenomenon of globalization emanating from the phenomenon of cosmic, in order to open up the prospects for possible historical reunification of the Islamic awareness in the first step, then the second step to build an applied contemporary Islam, which involves a wider comprehension of the theoretical and empirical problems confronting thought, reality and society in the world of Islam. The researcher found out that Arkoun intention was not to contribute to the expansion of our scientific knowledge about globalization, but to reach out whatever possible with the conditions of modern and contemporary reviving, and with the strategy of the original Enlightenment as the present and the future warn with great dangers, if we do not prepare ourselves, equivalently.